Transient and selective overexpression of D(2) receptors in the striatum causes persistent deficits in conditional associative learning - Bach, Mary-Elizabeth (National Academy of Sciences, 2008)
Cognitive deficits in schizophrenia are thought to derive from a hypofunction of the prefrontal cortex (PFC), but the origin of the hypofunction is unclear. To explore the nature of this deficit, we genetically modified mice to model the increase in striatal dopamine D(2) receptors (D(2)Rs) observed in patients with schizophrenia. Previously, we reported deficits in spatial working memory tasks in these mice, congruent with the working memory deficits observed in schizophrenia. However, patients with schizophrenia suffer from deficits in many executive functions, including associative learning, planning, problem solving, and nonspatial working memory. We therefore developed operant tasks to assay two executive functions, conditional associative learning (CAL) and nonspatial working memory. Striatal D(2)R-overexpressing mice show a deficit in CAL because of perseverative behavior, caused by interference from the previous trial. D(2)R up-regulation during development was sufficient to cause this deficit, because switching off the transgene in adulthood did not rescue the phenotype. We validated prefrontal dependency of CAL by using neurotoxic lesions. Lesions of the medial PFC including the anterior cingulate, infralimbic, and prelimbic cortices impair CAL because of increased interference from previously rewarded trials, exactly as observed in D(2)R transgenic mice. In contrast, lesions restricted to the infralimbic and prelimbic cortices have no effect on CAL but impair performance in the nonspatial working memory task. These assays not only give us insight into how excess striatal D(2)Rs affect cognition but also provide tools for studying cognitive endophenotypes in mice.